Dampak Kenaikan Pajak Pertambahan Nilai (PPN) Terhadap Konsumsi Rumah Tangga Menengah : Studi Empiris di Kota Besar - Ahmad Wahyudi Zein; Anju Andini; Valina Sinka (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The rise in Value Added Tax (VAT) from 11% to 12%, which was put into effect in January 2025, has elicited a range of reactions from Indonesian households, particularly those in the urban middle class. This research intends to investigate the effects of the VAT change on consumption habits among this group. Information was gathered through a survey conducted with 400 households in Jakarta, Surabaya, and Bandung utilizing a stratified random sampling technique. A quantitative analysis was performed using multiple linear regression. The findings indicate that while the overall tax burden on basic consumption did not rise significantly due to various mitigating measures, the public's perception of the VAT hike still resulted in a decline in spending—particularly on non-essential items and services. This result underscores the importance of fiscal perception in influencing household consumption patterns. The study suggests that fiscal transparency, public awareness campaigns, and compensatory policies are essential for preserving middle-class purchasing power during initiatives aimed at enhancing national tax revenue.